2021
DOI: 10.1111/ppe.12812
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 during pregnancy and associated outcomes: Results from an ongoing prospective cohort

Abstract: Background The COVID‐19 pandemic is an ongoing global health threat, caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Questions remain about how SARS‐CoV‐2 impacts pregnant individuals and their children. Objective To expand our understanding of the effects of SARS‐CoV‐2 infection during pregnancy on pregnancy outcomes, regardless of symptomatology, by using serological tests to measure IgG antibody levels. Methods The Generation C Study is an ongoing prospective cohort study conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
3
24
2
Order By: Relevance
“…Two of the IgG positive participants were also SARS-CoV-2 PCR positive (nasopharyngeal swab) at the time of the labor and delivery admission. Like in the larger Generation C cohort [19], IgG seropositive participants had higher pre-pregnancy BMI ( p =0.05) and were more often Hispanic, or non-Hispanic Black compared to IgG seronegative participants. In contrast, we did not observe differences in other maternal characteristics including age, parity, tobacco use, medical conditions, or obstetric conditions.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Two of the IgG positive participants were also SARS-CoV-2 PCR positive (nasopharyngeal swab) at the time of the labor and delivery admission. Like in the larger Generation C cohort [19], IgG seropositive participants had higher pre-pregnancy BMI ( p =0.05) and were more often Hispanic, or non-Hispanic Black compared to IgG seronegative participants. In contrast, we did not observe differences in other maternal characteristics including age, parity, tobacco use, medical conditions, or obstetric conditions.…”
Section: Resultsmentioning
confidence: 83%
“…Other studies show that active SARS-CoV-2 infection at delivery (mainly confirmed through a PCR positive test) is associated with obstetric and neonatal complications including increased risk of preterm birth, stillbirth, miscarriage, preeclampsia, emergency cesarean section and higher neonatal morbidity [8, 10-18]. However, in other reports, including ours from New York City and a Denmark study, SARS-CoV-2 IgG seropositivity without RT-PCR positivity at delivery was not associated with adverse pregnancy outcomes [19, 20].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To assess this, Molenaar and colleagues 4 documented seropositivity for SARS‐CoV‐2 virus during pregnancy in an ongoing, large prospective cohort study (the Generation C Study); 16% of pregnant persons in their large, US healthcare system tested positive for SARS‐CoV‐2 virus. After excluding prevalent infections detected at delivery, they found that SARS‐CoV‐2 positivity was neither associated with reductions in gestational age or Apgar scores, nor with increased risk of preterm birth, small for gestational age or NICU admission 4 . These results imply that observations of adverse foetal outcomes associated with maternal COVID‐19 could be more strongly linked with infection near the time of delivery.…”
Section: Estimating the Total Effects Of The Covid‐19 Pandemic On Mat...mentioning
confidence: 99%
“…In a national US-based validation study of diagnostic coding, Regan and colleagues 2 evaluated the performance of ICD-coded diagnoses and laboratory testing records In addition to concerns regarding exposure misclassification, studies that rely on viral detection at delivery will not include previously infected recovered individuals in their exposure assessments, resulting in selection bias. 1 To assess this, Molenaar and colleagues 4 documented seropositivity for SARS-CoV-2 virus during pregnancy in an ongoing, large prospective cohort study (the Generation C Study); 16% of pregnant persons in their large, US healthcare system tested positive for SARS-CoV-2 virus. After excluding prevalent infections detected at delivery, they found that SARS-CoV-2 positivity was neither associated with reductions in gestational age or Apgar scores, nor with increased risk of preterm birth, small for gestational age or NICU admission.…”
Section: E S Timating the Total Effec Ts Of The Covid -19 Pandemi C O...mentioning
confidence: 99%